2014
DOI: 10.1099/jmm.0.067496-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of hepatitis B virus and hepatitis C virus in human immunodeficiency virus type 1-co-infected patients from Venezuela

Abstract: The aim of this study was to evaluate the prevalence and genetic diversity of hepatitis B virus (HBV) and hepatitis C virus (HCV) in human immunodeficiency virus type 1 (HIV-1)-co-infected Venezuelan patients. The prevalence of HBV and HCV markers of infection in HIV-1 patients was 14 % for anti-hepatitis B core antigen, 3 % for hepatitis B surface antigen and 0.7 % for anti-HCV, respectively. HBV prevalence was higher than HCV, as expected for a country where sexual intercourse, not intravenous drug use, is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
7
1
1
Order By: Relevance
“…As was previously mentioned, the health of Warao population is widely affected by HBV, as well as by HIV-1 [ 23 ], which shares the same transmission routes. The HBV exposure prevalence in HIV-1 positive patients found in this study (33%), particularly in the male population, was higher than the one reported in the urban population of Venezuela (14%) and Colombia (12%) [ 50 , 51 ].…”
Section: Discussioncontrasting
confidence: 74%
“…As was previously mentioned, the health of Warao population is widely affected by HBV, as well as by HIV-1 [ 23 ], which shares the same transmission routes. The HBV exposure prevalence in HIV-1 positive patients found in this study (33%), particularly in the male population, was higher than the one reported in the urban population of Venezuela (14%) and Colombia (12%) [ 50 , 51 ].…”
Section: Discussioncontrasting
confidence: 74%
“…However, in this study, subgenotype F1b was notably present in 57% of the native cases (NOaxaca and NMichoacan) showing a closely genetic relatedness with other Latin American F1b strains. Other than the F1b cluster recently reported in Italy, this subgenotype that is more common among the western South American countries of Argentina and Chile has also been found in natives of Colombia and in Venezuela . Despite that HBV genotype H is most predominant in native Mexicans, the F1b strains found in Oaxaca were isolated from descendants of the ancient Mesoamerican Mixtecos.…”
Section: Discussionmentioning
confidence: 68%
“…Other than the F1b cluster recently reported in Italy,42 this subgenotype that is more common among the western South American countries of Argentina and Chile 17,19,43 has also been found in natives of Colombia 15 and in Venezuela 44. Despite that HBV genotype H is most predominant in native Mexicans, the F1b strains found in Oaxaca were isolated from descendants of the ancient Mesoamerican Mixtecos.…”
mentioning
confidence: 79%
“…Genotype G is not frequent in Latin America. In Venezuela, for example, only one isolate genotype G has been described, infecting an HIV-infected patient [ 36 ]. None of these Cuban patients were co-infected with HIV.…”
Section: Discussionmentioning
confidence: 99%